Role of EZH2 Polymorphisms in Esophageal Squamous Cell Carcinoma Risk in Han Chinese Population - Ma, Zhen-Bin (MDPI, 2014)
Gene single nucleotide polymorphisms play a critical role in the development of esophageal squamous cell carcinoma (ESCC). The aim of this study is to investigate the associations between EZH2 gene polymorphisms and ESCC risk. We undertook a case-control study to analyze three EZH2 polymorphisms (148505302C > T, 2110 + 6A > C and 626 − 394T > C) in an Han Chinese population, by extraction of genomic DNA from the peripheral blood of 476 patients with ESCC and 492 control participants, and performed EZH2 genotyping using DNA sequencing. The obtained results indicated that overall, no statistically significant association was observed in 148505302C > T and 2110 + 6A > C. However, 626 − 394T > C genotype was at increased risk of ESCCs (p = 0.006; odds ratio (OR) = 1.131, CI 95%: 1.034–1.236). Moreover, 626 − 394C/C genotype ESCCs were more significantly common in patients with tumor size of >5 cm than T allele ESCC and in cases of poor differentiation and lower advanced pathological stage. In conclusion, polymorphism in 626 − 394T > C was observed to be associated with susceptibility of ESCC. Nevertheless, further investigation with a larger sample size is needed to support our results.